2x/3+x-1/6=1-3(x-2)/4
Soluções para a tarefa
Respondido por
1
12 x/3 + 6x -1 = -18 (x-2/4)+6
6x + 12x/3 -1 = 18x-36/4 +6
10x - 1 = (9x-18)/2 +6
10x -1 = -9x+18+12/2
20x -2 = -9x+18+12
20x - 2 = -9x +30
20x = -9x + 32
29x = 32
x= 32/29
6x + 12x/3 -1 = 18x-36/4 +6
10x - 1 = (9x-18)/2 +6
10x -1 = -9x+18+12/2
20x -2 = -9x+18+12
20x - 2 = -9x +30
20x = -9x + 32
29x = 32
x= 32/29
Perguntas interessantes
Matemática,
1 ano atrás
Física,
1 ano atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás